Total neoadjuvant therapy in early-onset versus average-onset locally advanced rectal cancer: patient characteristics and tolerance of therapy☆ - M.L. Conces; N. Tursun; I. Ozgur; S. Yilmaz; D. Elamin; S. Patil; Y. Bouferraa; E. Gorgun; D. Liska; E. Weinstein; S.D. Kamath; S.R. Steele; et al. (ESMO Gastrointestinal Oncology)
Background: Patients with early-onset (EO, age <50 years) compared with average onset (AO, age ≥50 years) colorectal cancer have significantly higher rates of gastrointestinal toxicity with fluoropyrimidine and oxaliplatin therapy in the metastatic and adjuvant settings. Limited data exist regarding tolerance of total neoadjuvant therapy (TNT) when treating younger patients with locally advanced rectal cancer (LARC) despite the rising incidence of EO rectal cancer. Materials and methods: Data were abstracted from a retrospective database of patients with LARC treated with TNT from 1 January 2015 through 28 April 2021. Characteristics compared between EO and AO patients were demographic features, baseline characteristics of tumor, treatment delivery, antiemetic use, and toxicities. Results: Of 115 patients (39 EO, 76 AO), female patients constituted 51% of EO patients and 34% of AO patients (P = 0.077). No differences were found in race, ethnicity, clinical stage, dose of radiation or chemotherapy received, and antiemetic premedications and prescriptions. EO patients (versus AO patients) had more nausea (59% versus 28%, P = 0.001), fatigue (72% versus 47%, P = 0.013), and proctitis (28% versus 13%, P = 0.048) during chemoradiation and more nausea (69% versus 42%, P = 0.006) and stomatitis (21% versus 3.9%, P = 0.007) during chemotherapy. After adjusting for sex, EO patients were still at a greater odds of nausea compared with AO during chemoradiation (odds ratio 3.45, 95% confidence interval 1.51-7.69, P = 0.004) and chemotherapy (odds ratio 2.85, 95% confidence interval 1.28-6.67, P = 0.012). Conclusions: Patients with EO, compared with AO, LARC receiving TNT appear to have higher rates of nausea and should be considered for enhanced antiemetic regimens.